Associations of objectively measured sitting and standing with low-back pain intensity: a 6-month follow-up of construction and healthcare workers - Lars-Kristian Lunde; Markus Koch; Stein Knardahl; Kaj Bo Veiersted (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: This study aimed to determine the associations between objectively measured sitting and standing duration and intensity of low-back pain (LBP) among Norwegian construction and healthcare workers. METHODS: One-hundred and twenty-four workers wore two accelerometers for 3-4 consecutive days, during work and leisure. Minutes of sitting and standing was calculated from accelerometer data. We obtained self-reported LBP intensity (0-3) at the time of objective measurement and after six months. We examined associations with linear mixed models and presented results per 100 minutes. RESULTS: For healthcare workers, the duration of sitting during work [β= -0.33, 95% confidence interval (95% CI) -0.55- -0.10] and during full-day (work + leisure) (β= -0.21, 95% CI -0.38- -0.04) was associated with baseline LBP intensity. Furthermore, minutes of sitting at work (β=-0.35, 95% CI -0.57- -0.13) and during the full day (β=-0.20, 95% CI -0.37- -0.04) were significantly associated with LBP intensity at six months. Associations were attenuated when adjusting for work-related mechanical and psychosocial covariates and objectively measured exposure during leisure time. No significant associations between sitting and LBP intensity were found for construction workers. Standing at work was not consistently associated with LBP intensity at baseline or after six months for any work sector. CONCLUSIONS: This study suggests that a long duration of sitting at work is associated with lower levels of LBP intensity among healthcare workers. Standing duration had no consistent associations with LBP intensity.